Problematika Pengawasan Tindak Lanjut Putusan Bawaslu dan DKPP dalam Penegakan Hukum Pemilu - Rofi Aulia Rahman; Iwan Satriawan; Marchethy Riwani Diaz (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
Bawaslu is tasked with supervising the implementation of Bawaslu and DKPP decisions which must be followed up by KPU. The contrary of that during general elections in 2019 has created complications in the electoral law enforcement system. The research is focused to determine the legal certainty of follow-up to Bawaslu and DKPP decisions and form and scope of Bawaslu’s supervision of the follow-up. This is a qualitative descriptive analytical research with a normative and empirical juridical approach. The results indicate that in the implementation of Bawaslu and DKPP decisions is no legal certainty. The Constitutional Court have statement that the final and binding of DKPP decision applies to KPU, Bawaslu and President and its implementation is monitored by Bawaslu. The Bawaslu Regulation also does not accommodate in detail the mechanism for monitoring the follow-up, so it is necessary to have the regulation specifically.